Pharmaceutical Manufacturing Continuous Crystallization Procedures: A Review - N. Vaidya, Sunita (Asian Journal of Pharmaceutics (AJP), 2023)
This academic publication provides an overview of constant crystallization of solutions in the pharmaceutical industry. The comparison of continuous versus batch crystallizers, their construction benefits and drawbacks, and the addition of solid form framing to create a constantly focused interaction between digital advanced process technology technologies and chemical manufacturing functionalities were all covered in detail because of the broad key knowledge spectrum of precipitation. In-depth discussion was also given to mechanistic multiscale modeling, whose comprehension is crucial for the creation of future control applications. Process simulation and crystallizer optimization are also covered in the multiscale modeling section describes the model-based provided, which also addresses the intensifying method. Techniques the last section, is taken into consideration. The reader can become familiar with research pieces and their outcomes, which have thus far created different emerging viewpoints, by reading the unique articles on a particular theme that is gathered, talked about, and contrasted in the aforementioned primary categories. The pharmaceutical sector places a lot of emphasis on crystallization, and readers may already discover literature on continuous crystallization. However, due to the increasing trend towards the synthesis of items with special features that cannot be produced using conventional methodologies, the current study has placed a greater emphasis on the construction of automatic control for the generation of certain fine chemicals. Continuous crystallization may also allow for intensification techniques, modeling for optimization, “on-demand” production, and MPC. A classification study examines the literature.